Implementasi Model Cooperative Learning Tipe Tai Pada Mata Pelajaran Ipa Untuk Meningkatkan Sikap Percaya Diri Siswa Kelas Iv Sd Muhammadiyah 21 BaluwartiTahun Pelajaran 2016/2017 - Nuryatin, Arifin Sugiarti, Dra. Risminawati, M.Pd (2017)
This study aims to: 1) describe the implementation of cooperative learning model of TAI type in science subject in the fourth grade at SD Muhammadiyah 21 Baluwarti in the school year 2016/2017, 2) describe the increasing fourth grade students' self-confident through the implementation of cooperative learning model of TAI type of science subject at SD Muhammadiyah 21 Baluwarti in academic year 2016/2017. This research was a classroom action research. The echniques of data collection used servation,interviewsandocumentation. The data analysis used interactive analysis consisted of data reduction, data presentation and conclusion. The results showed that: 1) the implementation of cooperative learning model of TAI type there are 7 stages: pre-test, group, study material, study groups, counseling, debriefing, and post-test, 2) there is an increasing aplomb students with the mean average percentage of pre-cycle was only 38%, in the first cycle of 40% increased to 61%, while in the second cycle of 72% rising to 82%. The conclusion from this research was the implementation of cooperative learning model of TAI type can improve students' confident attitude of fourth grade students at SD Muhammadiyah 21 Baluwarti in the academic year 2016 / 2017.